Impaired Suppression of Sympathetic Activity during Fasting in the Gold Thioglucose-treated Mouse - Young, James B. (1980)
Sympathetic activity in rats and mice is diminished by fasting and increased by sucrose feeding. The central neural mechanisms coordinating changes in the functional state of sympathetic nerves with changes in dietary intake are unknown, but a role for neurons in the ventromedial hypothalamus (VMH) is suggested by the existence of sympathetic connections within the VMH and the importance of this region in the regulation of feeding behavior. To investigate the potential role of the VMH in dietary regulation of sympathetic activity [(3)H]norepinephrine turnover was measured in the hearts of fasted and sucrose-fed mice after treatment with gold thioglucose (AuTG). In control mice, norepinephrine (NE) turnover was 1.60±0.92 ng NE/heart per h (95% confidence limits) after 1 d of fasting and 4.58±0.98 after 3 d of sucrose feeding, although, in AuTG-treated mice, cardiac NE turnover in fasting was 5.45±1.56 and with sucrose feeding, 5.44±0.76. Experiments with ganglionic blockade indicate that the absence of dietary effect on NE turnover in AuTG-treated mice reflects a corresponding lack of change in central sympathetic outflow. AuTG administration, therefore, disrupts dietary regulation of sympathetic activity by abolishing the suppression of sympathetic activity that occurs with fasting. This effect of AuTG is unrelated to duration of fasting (up to 3 d) and is specific for AuTG because neither treatment with another gold thio compound (gold thiomalate) nor the presence of genetic obesity (ob/ob) prevented fasting suppression of sympathetic activity. Moreover, AuTG treatment did not impair sympathetic activation by cold exposure (4°C) nor adrenal medullary stimulation by 2-deoxy-d-glucose. Thus, AuTG treatment selectively impairs dietary regulation of sympathetic activity, possibly by destruction of neurons in the VMH.